The Seventh Finance Commission and Its Fault Lines (Asian Journal of Social Science Studies, 2016)
Bureaucracy is a vital institutional cog to foster Gross Domestic Product (GDP) and promote Human Development Index (HDI) in India. Of late its dysfunctionality and sub-serving character has been dismaying discerning sociologists like Merton & Parsons. The Seventh Finance Commission has also lamented this aspect while providing a bonanza to all, extending One Rank One Pension (OROP) to all categories of pensioners and improving the living conditions of the Group “C” employees. The paper brings out the novel aspects of the report like its emphasis on Skill India but laments about its inadequate attention to aspects like burgeoning Fiscal Deficit (FD) and lack of concern to improve productivity. The paper calls upon bureaucracy to follow the Weberian approach of being apolitical, rational and foster the process of shared prosperity through Rule of Law.